Emerging nuclear methods for historical painting authentication: AMS-14C dating, MeV-SIMS and O-PTIR imaging, global IBA, differential-PIXE and full-field PIXE mapping. (July 2022) - Calligaro, Thomas; Banas, Agnieszka; Banas, Krzysztof; Radović, Iva Bogdanović; Brajković, Marko; Chiari, Massimo; Forss, Anne-Maija; Hajdas, Irka; Krmpotić, Matea; Mazzinghi, Anna; Menart, Eva; Mizohata, Kenichiro; et al.
Abstract: There is a considerable interest in developing new analytical tools to fight the illicit trafficking of heritage goods and particularly of easel paintings, whose high market values attract an ever-increasing volume of criminal activities. The objective is to combat the illicit traffic of smuggled or forged paintworks and to prevent the acquisition of fakes or looted artefacts in public collections. Authentication can be addressed using various investigation techniques, such as absolute dating, materials characterization, alteration phenomena, etc.; for paintings this remains a challenging task due to the complexity of the materials (paint layers, ground, varnish, canvas, etc.) and preferable use of non-destructive methods. This paper outlines results from concerted action on detecting forged works of art within the framework of a Coordinated Research Project of the International Atomic Energy Agency (IAEA) called Enhancing Nuclear Analytical Techniques to Meet the Needs of Forensic Sciences 1 . One of the main objectives is to foster the use of emerging Nuclear Analytical Techniques (NAT) using particle accelerators for authentication of paintings, with potential application to other forensics domains, by highlighting their ability to determine painting authenticity and to track restorations or anachronistic clues. The various materials comprising a test painting were investigated using an array of NAT. Binder, canvas and support were directly dated by 14 C using Accelerator Mass Spectrometry (14C-AMS); binder and pigments' molecular composition was determined using Secondary Ion Mass Spectrometry with MeV ions (MeV-SIMS); paint layer composition and stratigraphy were accurately determined using Ion Beam Analysis (IBA) and differential Particle-Induced X-ray Emission (PIXE); and pigment spatial distributions were mapped using full-field PIXE. High resolution Optical Photothermal Infrared Spectroscopy (O-PTIR) molecular imaging was also exploited. Obtained results are presented and discussed. It is shown that the combination of the above-mentioned techniques allowed reconstructing the history of the test painting. Graphical Abstract: ga1